2018
DOI: 10.1111/ppc.12316
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of factors predicting nursing skills between general and psychiatric nurses

Abstract: Nursing education should facilitate other-consciousness in general nurses, but self-focus in psychiatric nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In the present study, associations of higher Reflection and Internal aspect, and lower Fantastic aspect subscale scores in the OCS were observed with higher nursing skills. A previous study 16 using a different sample reported that nursing competency levels among psychiatric nurses were predicted by higher scores on Reflection and Internal aspect subscales and lower scores on Fantastic aspect, while Reflection did not predict nursing competency levels among general nurses. The results of this study were in line with the previous study.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In the present study, associations of higher Reflection and Internal aspect, and lower Fantastic aspect subscale scores in the OCS were observed with higher nursing skills. A previous study 16 using a different sample reported that nursing competency levels among psychiatric nurses were predicted by higher scores on Reflection and Internal aspect subscales and lower scores on Fantastic aspect, while Reflection did not predict nursing competency levels among general nurses. The results of this study were in line with the previous study.…”
Section: Discussionmentioning
confidence: 72%
“…Pearson's correlation analysis was used to identify liner relationships between self-compassion and nursing competency after controlling for the effects of demographics, self-focus, and other-consciousness on nursing competency, which have been reported as influencing factors in a previous study. 16 Hierarchical regression analysis was conducted with nursing competency as the dependent variable. In Model 1, demographics were introduced as the only independent variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated in several studies, in order to improving their job performance, nurses must reflect on their own nursing care and behavior. Takase et al demonstrated that reflection has been shown to be positively related to nursing competence among nursing students in both a cross-sectional study and a longitudinal study [7,8]. The authors concluded that learning from reflection could be useful for both lesser and more experienced nurses, allowing them to embrace a positive view of their competence.…”
Section: Introductionmentioning
confidence: 99%
“…There is a robust, positive association between rumination and depression (Hasegawa et al, 2018). Furthermore, higher nursing skills in psychiatric nurses has been associated with higher reflection and lower rumination (Kurebayashi, 2019). Therefore, nursing educators should focus on preventing excessive rumination and enhancing self-reflection to improve nursing competencies among nursing students during their education.…”
Section: Introductionmentioning
confidence: 99%